Idiosinkrasi Pemikiran Hasan Langgulung dalam Membentuk Karakter Peserta Didik (Tinjauan Psikologi Pendidikan Islam) - Nasrulloh, Lalu Nasrulloh; Fuad, Ahmad Zakki; Abu Bakar, M. Yunus (Al-Riwayah : Jurnal Kependidikan, 2023)
Hasan Langgulung's thoughts in the development of students are quite taken into account, especially in Islamic education. Hasan Langgulung does not only emphasize cognitive aspects, but he also focuses on affective aspects. Thus, this is what distinguishes his concept of thought from other figures. The characteristic (idiosyncratic) of Hasan Langgulung's thoughts on education is the integration of psychology, philosophy and education. This characteristic is the purpose of writing an article entitled Idiosyncrasy of Hasan Langgulung's Concept of Thought on Student Development: An Overview of the Psychology of Islamic Education. The type of research used is library research, with an Islamic educational psychology approach. Sources of data in this study are books, articles, and other library sources, which are in accordance with the problems studied. The results found from this study are that Hasan Langgulung formulates his concept of thought in shaping the character of students, which is reflected in the three functions of Islamic education: spiritual, psychological, and social functions. On the other hand, Hasan langgulung also in transforming his thoughts did not forget to integrate with the philosophy of life. Key word: idionsyncrasi, Hasan Langgulung, character, Islamic psychology